Secondary immunoreaction in patients with neurosyphilis and its relevance to clinical outcomes - Fang, Yaxiu; Wu, Hong; Liu, Guanghui; Li, Ziang; Wang, Dongmei; Ning, Yuping; Pan, Suyue; Hu, Yafang (Frontiers in Neurology, 2023)
Background and purpose Several reported cases of autoimmune conditions such as anti-NMDAR encephalitis and neuromyelitis optica (AQP4) have been considered to be potentially secondary to Treponema pallidum infection. Since the role of immune impairment in neurosyphilis is unclear, in this retrospective study, we examined the correlation of the immune impairment in patients with neurosyphilis with their clinical characteristics and outcomes. Methods Clinical information was collected from patients with neurosyphilis in our center from January 2019 to December 2021. Cerebrospinal fluid (CSF) samples were subjected to indirect immunofluorescence tissue-based assay (IIF-TBA) on mouse brain sections and cell-based assay (CBA). The clinical characteristics and treatment outcomes of TBA-positive and-negative patients were compared. Results A total number of 81 patients diagnosed with neurosyphilis were included. The results of the CBA tests showed that three cases had anti-NMDAR, AQP4, or GAD65 antibodies, respectively. By TBA test, 38 patients (38/81, 46.9%) had positive immunostains, including staining of neuronal cells in 21 cases (21/38, 55.3%), glial cells in 11 cases (11/38, 28.9%), and neuronal and glial cells in six cases (6/38, 15.8%). We then compared the clinical characteristics and treatment outcomes between the TBA-positive and-negative patients and found that TBA-positive staining was significantly correlated with syphilis antibody titers (p = 0.027 for serum and p = 0.006 for CSF) and head MRI abnormalities (p < 0.001 for parenchymal abnormalities and p = 0.013 for white matter lesions). The cognitive prognosis of TBA-positive neurosyphilis patients was significantly worse than that of TBA-negative patients (p < 0.001). Conclusion The correlation between the TBA results and clinical data of our neurosyphilis patients imply the presence of secondary immune damage, which affected their prognosis. Therefore, TBA can be used as an additional biomarker for neurosyphilis patient prognosis.